Effects of water vapor and temperature on NOx and CO emissions during converter gas combustion. (15th November 2019) - Zhai, Yinghua; Li, Sen; Yan, Weiping; Wei, Xiaolin; Zhang, Leyu; Wang, Youtian
Highlights: The effect of water vapor concentration on converter gas combustion is investigated. Increasing water vapor concentration makes CO and NO emissions decrease. CO emission decreases sharply when C H2O, inlet increases from 0 to 0.4%. Abstract: Converter gas is a valuable fuel in the converter steelmaking process, and NOx and CO emissions are high due to the high temperature combustion and the absence of H2 O vapor. The effects of H2 O vapor concentration and the inlet temperature of converter gas on NOx and CO emissions in the combustion are investigated by a detailed chemical reaction mechanism. CO emission decreases sharply when C H2O, inlet increases from 0 to 0.4%. At C H2O, inlet > 0.4% and T inlet < 950 K, for the reduction of CO emission, the inlet temperature of converter gas is predominant over that of H2 O vapor in air. The inlet temperature of converter gas has noticeable influence on NO emission at C H2O, inlet < 2%. With the increase of C H2O, inlet, NO emission first increases, then reaches a peak value, finally decreases. At T inlet > 1050 K and C H2O, inlet > 2%, NO emission noticeably decreases with C H2O, inlet . In the presence of H2 O, H and OH free radicals are easily formed, the reduction path of NO is as follows: NO → NH/HNO → N2 .